Improved secure aware wormhole attack detection in mobile ad-hoc networks - M, Selladevi.; .T, Latha Maheswari; S, Duraisamy. (International Journal of Engineering and Technology, 2018)
The most challenging process in Mobile Ad-hoc Network (MANET) is detecting the wormhole attacks among various attacks. Most of the routing protocol doesn’t have any defence mechanism against wormhole attacks and thus the presence of such attacks may disrupt the network communication by transmitting the packets to unknown location. Different routing protocols have been proposed for wormhole attack detection and prevention based on the different requirements like hardware, synchronization clocks, etc. To avoid such requirements, a Secure Wormhole Attack Detection (SWAD) technique was proposed based on the maximum end-to-end delay computation between two nodes within the transmission range. However, it does not consider the path length which is significantly reduced by the wormhole attacks. Hence in this article, Improved Secure Wormhole Attack Detection (ISWAD) technique is proposed. In this scheme, length of paths from source to any destination is calculated with the maximum end-to-end delay between nodes. Based on both computations, wormhole links through the network is detected and the data is transmitted via an alternative path available in the routing table. Finally, the simulation results show that proposed ISWAD technique achieves better performance than the existing technique in terms of different network metrics like throughput, jitter, etc.